SEXO E DENSIDADE DE CRIAÇÃO SOBRE O DESEMPENHO DE FRANGOS DE CORTE COBB 500®, NA FASE DE CRESCIMENTO DE 21 À 35 DIAS DE IDADE - ANDRADE, Juliana Rocha; OLIVEIRA, Andréia Fróes Galuci; FERREIRA, Thales Silva; SILVA, Kelly Gabriela Pereira da; SANTOS, João Paulo Gomes; MARQUES, Ana Letícia Ribeiro (ANAIS DO ENIC, 2020)
-